2001
DOI: 10.1016/s0304-4203(01)00052-4
|View full text |Cite
|
Sign up to set email alerts
|

An automated photo-oxidation method for the determination of dissolved organic phosphorus in marine and fresh water

Abstract: A segmented flow automated method with on-line photo-oxidation for the determination of dissolved organic phosphorus+soluble reactive phosphorus (DOP+SRP) in seawater and fresh water is described here. A low-power lamp was used for a compact, easy-to-handle and low-ozone-producing manifold. The influence of seawater matrix components was studied in detail using natural seawater and salt solutions spiked with DOP model compounds. Bromide was found to be the most inhibitory species in seawater. The work shows th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 34 publications
0
32
0
Order By: Relevance
“…Traditional methods of digestion for natural water samples include fusion, dry ashing, perchloric acid, sulphuric acid-nitric acid and boiling on a hot plate, with more recent methods generally using autoclaving, UV photooxidation and microwave heating [75]. UV photo-oxidation can be used for organic phosphorus compounds in marine and freshwaters [47,76,77] but condensed polyphosphates present in the sample will not be broken down by UV photooxidation alone [2,3,78,79] and also need to be heated to 90-120 • C in the presence of acid [75]. To ensure that all polyphosphates present in the sample are decomposed, either boiling with HCl or potassium peroxydisulfate after UV irradiation is therefore recommended [80].…”
Section: Digestion Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional methods of digestion for natural water samples include fusion, dry ashing, perchloric acid, sulphuric acid-nitric acid and boiling on a hot plate, with more recent methods generally using autoclaving, UV photooxidation and microwave heating [75]. UV photo-oxidation can be used for organic phosphorus compounds in marine and freshwaters [47,76,77] but condensed polyphosphates present in the sample will not be broken down by UV photooxidation alone [2,3,78,79] and also need to be heated to 90-120 • C in the presence of acid [75]. To ensure that all polyphosphates present in the sample are decomposed, either boiling with HCl or potassium peroxydisulfate after UV irradiation is therefore recommended [80].…”
Section: Digestion Techniquesmentioning
confidence: 99%
“…This has important implications regarding decisions on the installation (or not) of costly phosphorus removal technology. Programmes involving multi-national participation and international databanks [76] require adequate quality assurance/quality control (QA/QC) schemes to ensure the data integrity necessary for the comparison of data from various sources. Adherence to QA guidelines, participation in inter-laboratory studies, use of reference materials (RMs) and certified reference materials (CRMs) are all means of achieving good data quality for phosphorus determinations [154,155].…”
Section: Quality Assurance and Quality Controlmentioning
confidence: 99%
“…However, seawater creates other problems affecting the batch analysis of samples. Indeed, the variable ionic strength and buffer capacity found along optical density gradients (from estuaries to coastal oceans and beyond) affect the pH of the mixed reagent plug flow to an unpredictable degree, particularly if no prior knowledge of the main characteristics of the analysed samples is held (Aminot et al ., 1997;Aminot and Kérouel, 2001;Woodward et al ., 2010). This usually affects the sensitivity of the analysis, and has to be tightly monitored by the analyst.…”
Section: Methodsmentioning
confidence: 99%
“…For samples such as soil waters, Peat et al [118] found that acidic photo-oxidation was required to avoid interference from higher concentrations of Fe and Al which can complex with phosphate. For marine waters, Aminot and Kerouel [121] reported that 5-6-fold dilution of sample was required in a SCFA photo-oxidation method for dissolved organic phosphorus in order to achieve full recovery of a series of model organic P compounds. This matrix effect was presumably due to interference from the high concentrations of Ca and Mg ions in seawater.…”
Section: Total Phosphorus and Dissolved Organic Phosphorusmentioning
confidence: 99%